2010
DOI: 10.1016/j.exger.2010.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress causes reversible changes in mitochondrial permeability and structure

Abstract: Mitochondria are a primary source as well a principal target of reactive oxygen species within cells. Using immunofluorescence microscopy, we have found that a number of mitochondrial matrix proteins are normally undetectable in formaldehyde fixed cells permeabilized with the cholesterol-binding detergent saponin. However, exogenous or endogenous oxidative stress applied prior to fixation altered the permeability of mitochondria, rendering these matrix proteins accessible to antibodies. Electron microscopy rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
2
19
0
1
Order By: Relevance
“…26 Apoptosis underlies neurodegeneration in dYME1L del flies. Mitochondrial dysfunction has been reported to trigger apoptosis in mammals.…”
Section: Resultsmentioning
confidence: 99%
“…26 Apoptosis underlies neurodegeneration in dYME1L del flies. Mitochondrial dysfunction has been reported to trigger apoptosis in mammals.…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts from patients with genetic mtDNA defects demonstrated that severe complex I deficiency yield increased ROS production was associated with mitochondrial fragmentation (79). Similarly, exposure of cultured cells to sublethal doses of exogenous ROS (H 2 O 2 ) induced mitochondrial fragmentation in mouse embryonic fibroblasts (MEFs) (31,73,92), neuronal cells (71), and in C 2 C 12 myocytes (47). …”
Section: Or Possibly By Other Nonmorphological Factors (See Altering mentioning
confidence: 99%
“…Cells were transiently transfected with Fugene 6 (Roche Applied Science) and incubated for 16 -30 h at 37°C. Staining of cells was performed as described (24). Cells were fixed in 3.7% formaldehyde for 20 -30 min at room temperature in 0.1 M sodium phosphate, pH 7.2, 150 mM NaCl.…”
Section: Expression Of Mouse Msra In Escherichia Coli and Hek293mentioning
confidence: 99%
“…M8032) until no color change occurred. Immunofluorescence staining was performed as described (24). Antibodies to MsrA (1:1000) and cytochrome c (1:500) were used for cell staining.…”
Section: Expression Of Mouse Msra In Escherichia Coli and Hek293mentioning
confidence: 99%